The Attalids of Pergamon and Anatolia : money, culture, and state power - Kaye, Noah, 1984- (Cambridge University Press, 2023)
Reveals how the iconoclastic Attalid dynasty of the ancient city of Pergamon ruled the Anatolian peninsula - and influenced our entire imagination of the Classical world - with only budgets, coins, and clever bureaucratic maneuvers, casting a single empire around Greek cities on the Aegean coast and indigenous villages on the steppe.